Integration of Multiliteracy of Islamic Education Teachers in Strengthening the Quality of Learning and Religious Character of Students in the Era of Educational Globalization - Dustnazar Omonovich Khimmataliev; Nilufar Pardaqizi Omonova; Akbar Namozovich Rasulov; Dilnura Sultonova (Indonesian Journal of Islamic Education Studies (INJURIES), 2025)
Educational globalization and digitalization have transformed the learning landscape, demanding Islamic Education teachers master multiliteracy to remain relevant. However, multiliteracy competency gaps remain obstacles in integrating technology with Islamic values. This study examines the integration of multiliteracy among Islamic education teachers as a key competency in enhancing learning quality and strengthening students' religious character in the era of educational globalization. Employing a qualitative library research approach, this research investigates the urgency of multiliteracy, conceptual strategies for integration, and the challenges and opportunities faced by teachers. The findings reveal that multiliteracy is crucial for enabling teachers to filter information, adapt digital learning technologies, and embed Islamic values in line with 21st-century educational demands. Key findings indicate: (1) multiliteracy enhances learning effectiveness by up to 40% through TPACK integration, (2) teachers with multiliteracy competence develop students' religious character 35% more effectively, and (3) multiliteracy-based PjBL strategies increase student engagement by up to 50%. Conceptual integration strategies include curriculum development, digital technology utilization, project-based learning, and inter-teacher collaboration. The main challenges consist of limited digital skills, resistance to change, and insufficient continuous professional training. However, significant opportunities emerge from educational policy support, access to digital resources, and the reinforcement of religious moderation. This study contributes to the theoretical development of multiliteracy in Islamic education while offering practical implications for teachers, educational institutions, and policymakers. Practical implications include: (1) for teachers - concrete guidelines for implementing multiliteracy in Islamic education learning, (2) for institutions - frameworks for curriculum development and multiliteracy-based training, and (3) for policymakers - recommendations for regulations and budgets to strengthen digital competencies of Islamic education teachers.